THE HUMANISTIC VALUES OF THE POHAMBA-HAMBA LOCAL WISDOM OF BUTON COMMUNITY AS A FOUNDATION FOR CHARACTER BUILDING - La Dunifa; Sahlan Sahlan (Jurnal Sosial Humaniora, 2021)
Pohamba-hamba (mutual-servant) is one of the local wisdom of the Buton community. It has spread throughout the territory of the Sultanate of Buton years ago. However, nowadays, the humanistic values ​​of this local wisdom are fading. Individualistic lifestyles, especially among the younger generation, are increasingly prominent. The present study is delved to reveal (1) the types of the pohamba-hamba local wisdom (PLW) which are still preserved by the local community; and (2) to reveal the humanistic values contained in the PLW. This study uses an ethnographic approach, with sociological and hermeneutic analysis methods. Twelve persons from different occupations and educational backgrounds participated in this study. The data ware collected using interviews, participant observation, and (c) documentation. The research reveals that three types of the PLW are still preserved by the local community, namely: (1) planned pohamba-hamba; (2) the alternating pohamba-hamba; and (3) spontaneous pohamba-hamba. They are three humanistic values contained in PLW: (1) togetherness, (2) sincerity, and (3) empathy. The implication and suggestions for future research are discussed.